TANGGUNG JAWAB PELAKU USAHA SEBAGAI PEMESAN DAN PEMBUAT IKLAN TERHADAP IKLAN YANG MERUGIKAN KONSUMEN - Geya Aditya Rachman, Gede; Puspawati, I Gusti Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 06, Juli 2013, 2013)
This paper is titled “Responsibilities of Bussiness Actor as an Advertiser Toward the Advertisment that Incur Losses for the Consumer”. This paper uses analytical method and statute approach. Bussiness actor uses the advertisement to promote their goods and services to the consumer. The advertisement hold a big role in inreasing the number of selling. However, bussiness actor as the advertiser often ignoring the conditions about the procedures of making the advertisement that ncur losses for the consumer. Therefore, good bussiness actor are being responsible of a losses that experienced by the consumer.
Keywords: Responsibility, Advertisement. Losses